Perlindungan Terhadap Anak Sebagai Korban Dating Violence Ditinjau dalam Perspektif Hukum Pidana dan HAM - Fara Syahrani; Hania Arvalia (Journal of Sharia and Legal Science, 2025)
The phenomenon of dating violence has not received much attention from the public. This study aims to analyze the forms of dating violence that are categorized as human rights violations and to examine the criminal liability of perpetrators as well as protection for child victims. The research method used is normative juridical with descriptive analytical specifications using a qualitative analysis approach with legal interpretation. This research provides new insights by specifically examining dating violence and its relationship to human rights, as well as legal accountability and protection. The results of the study show that forms of dating violence against children are categorized as human rights violations. Although there are currently no specific regulations regarding dating violence, accountability and protection can be carried out through existing legal frameworks such as the Criminal Code, the Child Protection Law, and the TPKS Law. This study recommends the existence of specific regulations related to dating violence to strengthen the protection of children, not to legalize dating among children, but as a response to the existing practice of dating that has been prevalent in society.